PERSEPSI GURU TENTANG PELAKSANAAN FUNGSI KEPEMIMPINAN KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN SUNGAI TARAB - Hermi Elvira (Jurnal Bahana Manajemen Pendidikan, 2017)
The purpose of this research was look information about the teacher perception about implementation of the principal’s leadership function on elementary school . This is a descriptive research. The population is 175teachers and research sample is 76teachers that taken by Slovin formula.The instrument of thisresearch was a questionnaire with Likert scale models that had tested for validity and reliability. Data analyzed using the average (mean)formula. The resultsof this research show teacher perception about implementation of the principal’s leadership function on elementary school (SDN)in Sungai Tarab stay in  good enough category with an average score 3,42.Keywords: Perception, leadership function